Clinical characteristics of asymptomatic and symptomatic COVID-19 patients in the Eastern Province of Saudi Arabia - Jumana Mansour AlJishi; Alya Hassan Alhajjaj; Fatimah Lateef Alkhabbaz; Taaweel Hussain AlAbduljabar; Ahmad Alsaif; Hussain Alsaif; Kawther Saeed Alomran; Ghada Ali Aljanobi; Zainab Alghawi; Mohammed Alsaif; Jaffar A. Al-Tawfiq (Elsevier, 2021)
Background: The first case of COVID-19 infection in Saudi Arabia was reported in Qatif on March 2nd, 2020. Here, we describe the clinical characteristics of the initial COVID-19 patients in that area. Methods: This is an observational study describing the clinical presentation, radiographic and laboratory data of COVID-19 cases. Results: From March 1st, 2020 to April 5th, 2020 we identified a total of 82 adult COVID-19 patients. The median age of the patients was 50 years, with a range of 30 to 60 years and most of patients were female 54 (65.9%). Of all the patients, 29 (35.4%) were contacts and 43 (52.4%) were returning travelers, mainly from Iraq (65% of the total returning travelers). Comorbidities were present in 50% of patients, G6PD deficiency in 33%, hypertension in 27%, and diabetes mellitus in 26%. Chest radiographs were abnormal in 46% of symptomatic and 15.5% of asymptomatic patients (P value = 0.0035). Of all patients, 4 (4.87%) required intensive care admission. There was no significant difference in time to negative RT-PCR with mean days to negativity of 13.6 and 16.9 for asymptomatic and symptomatic group, respectively (P value = 0.42). Conclusions: In the initial Epicenter of the COVID-19 in Saudi Arabia, the majority of the patients were asymptomatic and were returning travelers. Comorbidities were present in nearly half of the patients.